Predictors of Environmental Awareness Among Preschool Children - Ismail Elhadidi, Ekhlass Abdulla Ahmed; Ali Hassan, SalwaAbass; Ahmed, Fatma Mohammed (Journal of Neonatal Surgery, 2025)
Background: Today’s world is witnessing environmental issues such as Global warming, polluted water, and climate change etc. Those issues have reached alarming levels due to human maltreatment of natural resources. Hereafter, meeting the needs of the present without compromising the ability of future generations to meet their own needs is crucial. Hence, sustainable awareness and environmental literacy at early ages are vital. The aim of this study was to assess predictors of environmental awareness among preschool children. Methodology: Descriptive design was used to conduct the study on 80 preschoolers at 5 governmental nursery schools. Tools of data collection: structured questionnaire sheet consists of two parts they are demographic characteristics and environmental awareness Results: The study revealed that83.7% of preschool children had poor home conditions, totally none (0.0%) of them had environmental awareness. Conclusion: Preschool children were entirely unaware environmentally. Recommendations: Replicate the study in other settings and on larger sample to permit generalization. Conduct interventional programs to raise preschoolers’ awareness about environment.